Identification of Ferroptosis-Related Molecular Clusters and Immune Characterization in Autism Spectrum Disorder - Liu, Lichun; Lai, Yongxing; Zhan, Zhidong; Fu, Qingxian; Jiang, Yuelian (Frontiers in Genetics, 2022)
Introduction: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with clinical presentation and prognostic heterogeneity. Ferroptosis is a regulated non-apoptotic cell death program implicated in the occurrence and progression of various diseases. Therefore, we aim to explore ferroptosis-related molecular subtypes in ASD and further illustrate the potential mechanism. Methods: A total of 201 normal and 293 ASD samples were obtained from the Gene Expression Omnibus (GEO) database. we using the unsupervised clustering analysis to identify the molecular subtypes based on ferroptosis-related genes (FRGs), and evaluate the characteristics of immune between ferroptosis subtypes. Ferroptosis signatures were identified using the least absolute shrinkage and selection operator regression (LASSO) and recursive feature elimination for support vector machines (SVM-RFE) machine learning algorithms. The ferroptosis scores based on seven selected genes were constructed to evaluate the ferroptosis characteristics of ASD. Results: We identified 16 differentially expressed FRGs in ASD children compared with controls. Two distinct molecular clusters associated with ferroptosis were identified in ASD. Analysis of immune infiltration revealed immune heterogeneity between the two clusters. Cluster2 characterized by a higher immune score and the larger number of infiltrated immune cells exhibited stronger immune response, and it was markedly enriched in immune response-related signaling pathways. Additionally, the ferroptosis scores model was capable of predicting ASD subtypes and immunity. Higher levels of ferroptosis scores were associated with immune activation, as seen in Cluster2. lower ferroptosis scores were accompanied by relative immune downregulation, as seen in Cluster1. Conclusion: Our study systematically elucidated the intricate correlation between ferroptosis and ASD and provided a promising ferroptosis scores model to predict the molecular clusters and immune infiltration cells profiles of children with ASD.